Inovasi Kurikulum dalam Upaya Meningkatkan Mutu Pendidikan di Indonesia - Aisyah Faradhilah Yasmin; Atika Maulidina Hs (STKIP AL HIKMAH SURABAYA, 2023)
Curriculum is a very important role in education aimed at directing it in a better direction. Curriculum implementation is developed in schools to suit circumstances and needs. These things are related to each other and become a reference for all parties who play a role in implementing the curriculum. The curriculum process includes planning, organizing, implementing, monitoring and evaluating in curriculum development. Evaluation as a measure of curriculum achievement. Education is a human effort to improve knowledge to become better. The purpose of this article is to develop an innovative curriculum in an effort to improve the quality of education.